Improving Students’ Digital Literacy in a Suburban Elementary School: An Action Research Study within a Community Service Program - Aang Subiyakto; Sulaiman Haris; Anisya Rahma (Sagamedia Teknologi Nusantara, 2026)
The increasing integration of digital technology in elementary education presents both opportunities and risks for students’ cognitive, social, and behavioral development. This study aimed to examine the digital literacy status of elementary school students in terms of engagement, understanding, behavior, digital awareness, and reflection, and to enhance these dimensions through a classroom-based seminar intervention implemented as action research within a community service program. The study involved 18 sixth-grade students from a suburban elementary school in Banten Province, Indonesia. An educational and participatory approach was employed, incorporating structured material presentations, interactive discussions, guided practical activities, visual media, and formative quizzes. The findings indicate that the seminar-based intervention contributed to measurable improvements in students’ digital engagement, understanding, behavior, and digital awareness. However, the development of critical reflection required further iterative cycles of action-based learning. These results provide empirical support for participatory classroom interventions as a viable strategy for strengthening digital literacy as a foundational competency at the elementary school level.